Poly(butylene terephthalate) for Laser Powder Bed Fusion of Polymers: Feedstock Precipitation and Powder Characterization - Tischer, Florentin; Düsenberg, Björn; Kaschta, Joachim; Bück, Andreas; Peukert, Wolfgang; Schmidt, Jochen (ACS Applied Polymer Materials, 2024)
Powder bed fusion of polymers with a laser beam (PBF-LB/P) is a layer-based additive manufacturing method that excels in producing functional components of complex geometries. However, the limitation of commercially available materials to mostly polyamides reduces the range of applications for PBF-LB/P-processed parts. Recently, liquid−liquid phase separation and crystallization have been reported as a suitable method to produce poly(butylene terephthalate) (PBT) microparticles of good flowability as a PBF-LB/P feedstock. PBT is an interesting plastic feedstock as its properties allow for an extension of the application of AM-built parts in the automotive and electronics sectors. Starting from PBT feed materials with different molar mass distributions, we investigate the effect of the feed material used in the thermal precipitation process under otherwise identical process parameters on the resulting PBT powder properties. The thermal precipitation process is highly robust with respect to bulk solid properties, such as particle size distribution, particle shape, flowability, and intrinsic properties (crystal structure and melting behavior). These product characteristics are virtually unaffected by the average molar mass of the PBT feed. Melt crystallization is accelerated, while the viscosity decreases with decreasing molecular mass. Once favorable process conditions are defined, which lead to powders with suitable properties, the crystallization kinetics and melt viscosity can be adjusted accordingly without changing the powder properties. Key parameters, which influence part porosity (through melt coalescence), layer adhesion, or the tendency of the material to warp during the PBF-LB/P process, are adjustable to produce a customized starting materia
Keywords: powder characterization; powder production; poly(butylene terephthalate); powder bed fusion; liquid−liquid phase separation